Causes of motor system overload in step aerobics: Literature review - Rutkowska-Kucharska Alicja (Sciendo, 2017)
Many publications have indicated the positive impact of step aerobics on health. Although step aerobics aims to improve endurance and other health parameters, injuries incurred from overload happen to both instructors and participants. Values of vertical ground reaction force (vGRF) while stepping on and off the bench do not lead to overload on the motor system - they are similar to the values obtained for walking or stair climbing. One reason for injuries may be the step workout technique. Overloads may be caused by incorrect technique of foot positioning on the bench, small knee angle during stepping off, and small angle of trunk flexion. This study presents an overview of current research on the load of the motor system in step aerobics.